REFRAMING EDUCATIONAL CITIES AS WASTE GOVERNANCE LABORATORIES - Suyeno, Suyeno; Putra, Langgeng Rachmatullah; Ngindana, Rispa; Kumalasari, Ima (UI Scholars Hub, 2025)
Rapid urban growth in mid-sized cities within developing countries has increased challenges in municipal solid waste management, especially in urban areas known for their concentration of educational institutions and dense populations. This study aims to evaluate the effectiveness of these policies through the framework of Good Environmental Governance, identifying critical gaps in policy implementation and proposing sustainable solutions. This study employs Soft Systems Methodology, a participatory approach for exploring complex, ill-structured problems. The key steps included rich picture creation, root definition, conceptual modeling, and comparison with real-world practices. This allowed for the integration of stakeholder perspectives and the identification of feasible, context-specific interventions that were gathered from key stakeholders through in-depth interviews. The findings show substantial disparities between regulatory frameworks (de jure) and their practical application (de facto), evidenced by low compliance rates in household waste separation, limited institutional coordination, underdeveloped 3R (reduce, reuse, and recycle) infrastructure, and deeply rooted community habits that hinder effective waste management. This study proposes a conceptual model for integrating community-based recycling systems, strengthening the 3R infrastructure at the grassroots level, and fostering sectoral collaboration. Moreover, this study aims to promote the establishment of a City Waste Governance Task Force co-led by universities, local governments, and community groups to strengthen cross-sectoral coordination; implement performance-based incentives for neighborhood associations that achieve waste separation and recycling targets; and develop a municipal waste data dashboard managed jointly by student research centers and the Environmental Agency to enhance transparency and real-time tracking.